Cross-border transport infrastructure, regional integration and development - Manabu Fujimura (Asian Development Bank Institute (ADBI), 2004)
The paper discusses salient features involved in the recently proliferating initiatives of regional economic integration, especially in transport infrastructure and trade facilitation. It first conceptualizes causal relationships among cross-border transport infrastructure, trade costs, trade and investment, and economic growth, and then distributional issues involved in achieving cooperation toward the virtuous circle. It then discusses institutional and financing issues of the cooperation. Asymmetric benefit-cost distribution may arise due to differences in geography, economic size, institutional history and capacity. While cross-border transport infrastructure may be classified as a club good, careful institutional and financial arrangements are called for in its successful provision. Case studies from the Mekong and Central Asia regions are provided. Then the paper points to some directions for promising future research.
Keywords: 330; Grenzüberschreitender Güterverkehr; Verkehrsinfrastruktur; Wirtschaftsintegration; Handelsregionalismus; Entwicklung